Single and periodic overloading effects on the mode I fatigue crack growth of a ductile adhesive. (October 2022) - Sousa, F. Castro; Akhavan-Safar, A.; da Silva, L.F.M.
Abstract: Variable amplitude fatigue loading, where overloading is included, is commonly experienced by bonded structures. Thus, this work aims the assessment of the influence of overloads on the total fatigue life and fatigue crack growth (FCG) of a ductile adhesive. Double cantilever beam (DCB) specimens were subjected to different fatigue loading spectra including constant amplitude, single and periodic overloads. Stiffness degradation and its rate variation were also evaluated. Results showed that overloads can have a fatigue retarding effect leading to an increase in fatigue life up to 4 times. However, for periodic overloads, this increase in fatigue life was less pronounced. Highlights: The influence of overloads on the total fatigue life and fatigue crack growth of a ductile adhesive was investigated. Double cantilever beam (DCB) specimens were subjected to different fatigue loading spectra. Overloads can have a fatigue retarding effect leading to an increase in fatigue life up to 4 times. For periodic overloads, the increase in fatigue life was less pronounced. The higher the plastic zone caused by the overload, the higher the retardation.